060 Ethics and neurology. Issue 3 (9th February 2012) - Baker, K; Hughes, T A T
Abstract : Ethical issues are highly relevant in neurology, which has often been a source of difficult cases. The nature of neurological disease means that capacity may be affected earlier than in other diseases. Neurology patients may have currently incurable disease and may be vulnerable to unethical suggestions for new treatments. In view of this we have developed an ethical checklist which focusses on the most common ethical problems that are encountered on the neurology ward in a simple and practical way, and can be used at admission: Confidentiality is a fundamental concept within medical ethics. However there are occasions when it can legitimately be broken, for example, a patient driving despite uncontrolled seizures. Capacity is the ability to take a particular decision. We are obliged to provide support to patients to enable their capacity, and all doctors should be able to assess capacity. Consent requires capacity. Patients are often asked to consent to invasive procedures for example, brain biopsy or LP. Conflicts may exist between patient and family, or between patient and staff. End of life: Is this patient being admitted because they are in a terminal stage of their disease? Should resuscitation be discussed? Do they have an advance decision or an attorney appointed? Further information may be needed from the patient, their family or GP. Incorporating this checklist into clerking will allow ethical issues to be addressed in a structured and timely manner, and enhance overall management of patients.